Some results of a class of univalent functions with negative coiffitions - Fadhel, Mustafa; Buti, Rafid (International Journal of Applied Mathematical Research, 2014)
In this paper, we study a new subclass of univalent analytic functions with positive coefficients in the unit disk; we obtain main result, distortion theorem and some properties of this subclass. Keywords: Univalent Functions, Distortion Theorem, Linear Combination.